2019
DOI: 10.12962/j20882033.v30i3.5496
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Bending Analysis of Steel/Resin-Talk Sandwich Material

Abstract: Sandwich material can be used as the substitute for the ship conventional material. The core sandwich material used in this study consisted of a talk-resin-catalyst. The core mixture proportion is 90% resin and 10% talk. A thick steel plates is used as the face of the core sandwich material. Both experimental and numerical simulations are carried out to investigate the bending or flexural behavior of the proposed sandwich material. Three-point bending test has been carried out to determine the yield stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Combining these two material characteristics creates a sandwich effect that provides a very efficient ratio of stiffness-to-weight [3,4,5], which is an important characteristic for light structures in the ship's construction [6]. In terms of the development of SPS for ship structure, several core materials have been analyzed, such as the combination of unsaturated polyester resin (UPR) with talc powder [7], bio-resin using vinyl ester and vegetable oil [8,9], UPR with a clamshell powder [10], UPR with an eggshell powder [11], epoxy resin [6], and polyurethane elastomer (PU) [12,13,14]. Steel faceplates and room temperature cured polyurethane elastomer core are commercial materials of SPS for ship structure [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…Combining these two material characteristics creates a sandwich effect that provides a very efficient ratio of stiffness-to-weight [3,4,5], which is an important characteristic for light structures in the ship's construction [6]. In terms of the development of SPS for ship structure, several core materials have been analyzed, such as the combination of unsaturated polyester resin (UPR) with talc powder [7], bio-resin using vinyl ester and vegetable oil [8,9], UPR with a clamshell powder [10], UPR with an eggshell powder [11], epoxy resin [6], and polyurethane elastomer (PU) [12,13,14]. Steel faceplates and room temperature cured polyurethane elastomer core are commercial materials of SPS for ship structure [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…An example of this application is found in the work of Numerical and Experimental Validation of Bending in a Resin Steel Sandwich Structure for bulkheads and structural members, where the real behavior is compared with the numerical one and allows according to the authors to observe the behavior curve of the material and the process of failure and subsequent cracking [4]. In the same way, in other studies observed, structures and plates of any vessel in composite material are evaluated and allow to validate the results generated by the FEM, such as the specifi c case of the experimental and numerical fl exion analysis of steel/resin sandwich material, which looked for to confront the real results with the FEM.…”
mentioning
confidence: 99%